2012
DOI: 10.1080/09658211.2012.690039
|View full text |Cite
|
Sign up to set email alerts
|

Children's memory distortions following social contact with a co-witness: Disentangling social and cognitive mechanisms

Abstract: This study examined whether recalling an event with a co-witness influences children's recall. Individual 3-5-year-olds (n = 48) watched a film with a co-witness. Unbeknown to participants, the co-witness was watching an alternative version of the film. Afterwards both the co-witness and the participant answered questions about the film together (public recall), and the degree to which children conformed to the co-witness's alternative version of events was measured. Subsequently participants were questioned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Effect sizes appear to decrease from a 1‐hour retention interval versus more than 24 hours, and age differences may be more pronounced when the stimulus does not induce stress. The size of the social conformity effect found in the present study was dramatic and on par with that found by Bright‐Paul, Wright, and Guillaume () for preschool‐aged children (overall 32% conformity errors) and with 6 to 12‐year‐olds (Candel et al, ; 60% incorporating at least one detail from peer's report). Bright‐Paul and her colleagues employed a logic similar to that used in this study, separating the errors made during the time 2 private interviews from those errors made in the group setting and concluded that one third of errors were due to social conformity and two thirds due to memory distortion caused by listening to a cowitness.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Effect sizes appear to decrease from a 1‐hour retention interval versus more than 24 hours, and age differences may be more pronounced when the stimulus does not induce stress. The size of the social conformity effect found in the present study was dramatic and on par with that found by Bright‐Paul, Wright, and Guillaume () for preschool‐aged children (overall 32% conformity errors) and with 6 to 12‐year‐olds (Candel et al, ; 60% incorporating at least one detail from peer's report). Bright‐Paul and her colleagues employed a logic similar to that used in this study, separating the errors made during the time 2 private interviews from those errors made in the group setting and concluded that one third of errors were due to social conformity and two thirds due to memory distortion caused by listening to a cowitness.…”
Section: Discussionsupporting
confidence: 75%
“…If it turned out that children conformed to adult pressures, then it would rule out the failure to monitor ambient discussion hypothesis and suggest that the basis for the present findings was the deferral of their own memory to the memory of someone they assume is superior—an older person. Importantly, the impact of peer influence is likely mediated by individual difference variables, such as theory of mind, personality variables, and inhibitory control (Bright‐Paul et al, ; Chae & Ceci, ; Schneider, ).…”
Section: Discussionmentioning
confidence: 99%
“…Memory researchers have employed three approaches to examine the co-witness suggestibility effect. In one approach, participants watch a video of a crime with a confederate who subsequently provides the misinformation (Bodner, Musch, & Azad, 2009;Bright-Paul, Jarrold, Wright, & Guillaume, 2012;Jack, Zydervelt, & Zajac, 2014;Paterson & Kemp, 2006;Paterson et al, 2012). In a second approach, participant pairs watch a video on separate screens and (unbeknownst to them) view different versions of the video (Gabbert et al, 2003;Gabbert, Memon, & Wright, 2006;see Wright, Memon, Skagerberg, & Gabbert, EYEWITNESS MEMORY FOLLOWING DISCUSSION 6 2009, for a review).…”
Section: In Ten Countriesmentioning
confidence: 99%
“…These children were a subset of children (n = 188) who took part in a study of children's reporting of salient experiences (see Rush et al, 2015). This age range was selected because it spans the bridge between the preschool and early school years during which important decreases in susceptibility to suggestion (Bruck & Ceci, 1999) and internalization of parental reminiscing style (Reese et al, 1993) occur. We capped the age range at 7 years of age because pilot testing indicated that children older than 7 years were skeptical about the toy breakage procedure and correctly guessed that the toys were rigged to break.…”
Section: Participantsmentioning
confidence: 99%
“…Finally, the interviewer asked about specific actions and breakage with each of the toys. These latter questions included suggestive questions, defined as those containing a false supposition and implying an expected response, in line with previous literature on children's suggestibility (Bruck & Ceci, 1999;Goodman & Reed, 1986;Lamb et al, 2007). There were six suggestive questions about false elements of the interaction (e.g.…”
Section: Interviewer-child Interviewmentioning
confidence: 99%